Defects in halide perovskites: The lattice as a boojum?. (June 2020) - Kumar, Sujit; Hodes, Gary; Cahen, David
Abstract: Abstract : Although halide perovskites (HaPs) are synthesized in ways that appear antithetical to those required for yielding high-quality semiconductors, the properties of the resulting materials imply, particularly for single crystals, ultralow densities of optoelectronically active defects. This article provides different views of this unusual behavior. We pose the question: Can present models of point defects in solids be used to interpret the experimental data and provide predictive power? The question arises because the measured ultralow densities refer to static defects using our present methods and models, while dynamic defect densities are ultrahigh, a result of the material being relatively soft, with a shallow electrostatic energy landscape, and with anharmonic lattice dynamics. All of these factors make the effects of dynamic defects on the materials' optoelectronic properties minimal. We hope this article will stimulate discussions on the nontrivial question: Are HaPs, and especially the defects within them, business as usual?